The practice of corporate social performance in minority- versus nonminority-owned small businesses - Thompson, Judith Kenner (Journal of business ethics, 1993)
This study compares corporate social performance in terms of charitable contributions of minority-owned and nonminority-owned small businesses. In this sample, minority-owned small businesses are younger, have less full-time employees, and lower annual sales. Minority-owned small businesses donate more funds to religious organizations than nonminority-owned small businesses. When annual sales are accounted for, minority-owned businesses contribute more total dollars to all charitable organizations than nonminority-owned firms. Suggestions for future research in this area are delineated.